2009
DOI: 10.1111/j.1365-2702.2009.03038.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between nurse care‐giving behaviours and preterm infant responses during bathing: a preliminary study

Abstract: How nurses take care of the preterm infants influences their responses to care-giving stimuli. To interact better with the infant during care-giving procedures, nurses need to provide more supportive care-giving behaviours especially 'position support' and 'containment' based on the infant's needs, and avoid care-giving that may be too rough and occur too quickly without attending the baby's stressful signals, positioning the baby in hyperextension posture, or chatting with other people during procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
3
15
0
2
Order By: Relevance
“…Our study findings are similar to a report that QS increased when the infant was alone with no caregiving offered, and waking states increased when the infant was with caregivers (Brandon et al, 1999). Our results are also consistent with reports that with more intrusive caregiving, infants' fussy, or crying state increased (Brandon et al, 1999;Liaw, Yang, Chou, Yang, & Chao, 2010;Liaw, Yang, Yuh, & Yin, 2006). In the present study, the occurrence of infants' wake and fussy or crying states increased with increasing frequency of intrusive caregiving.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study findings are similar to a report that QS increased when the infant was alone with no caregiving offered, and waking states increased when the infant was with caregivers (Brandon et al, 1999). Our results are also consistent with reports that with more intrusive caregiving, infants' fussy, or crying state increased (Brandon et al, 1999;Liaw, Yang, Chou, Yang, & Chao, 2010;Liaw, Yang, Yuh, & Yin, 2006). In the present study, the occurrence of infants' wake and fussy or crying states increased with increasing frequency of intrusive caregiving.…”
Section: Discussionsupporting
confidence: 83%
“…Both routine and intrusive caregiving may stress infants and increase their arousal and fussiness (Brandon et al, 1999;Liaw et al, 2010;Liaw et al, 2006;Peters, 1998). As infants' arousal and fussiness increase, their motor movements increase, in turn increasing their metabolic rates as well as oxygen and energy consumption (Lehtonen & Martin, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Supportive handling decreases infant stress compared with rough or careless handling. 6 Careful assessment of infant stress cues and readiness for interaction led to a new approach to caregiving termed "developmental care." 7 However, Peters 8 concluded that developmental care approach had not radically changed infant handling in the NICU.…”
Section: Neonatal Intensive Care Unit Infant Handlingmentioning
confidence: 99%
“…During painful caregiving procedures, preterm infants lack the autonomic and functional maturity to regulate themselves (Liaw et al, 2012a;Gibbins et al, 2008), so they need more support and protection to comfort them and facilitate their behavioural stability (Liaw et al, 2010;Catelin et al, 2005). Such support and protection has been shown to relieve mild-tomoderate short-term pain and comfort infants in distress by nonpharmacological interventions such as NNS (Liaw et al, 2012b), oral sucrose (Cignacco et al, 2012;Stevens et al, 2010), and FT (holding an infant with warm hands to offer tactile and thermal sensory stimulation; Liaw et al, 2012b;Axelin et al, 2006).…”
Section: Introductionmentioning
confidence: 98%